Do climate change policies, and environmental regulations affect the financial performance: policy-based analysis in context of green innovation - Yang, Li; Shahzadi, Irum [UNESP]; Feng, Xiaowei; Nassani, Abdelmohsen A. (My University, 2024)
In these modern times, developed and developing economies use different means and strategies to attain economic growth and financial development. Still, environmental recovery instruments are not yet empirically explored in developed regions. The prime objective of this study is to unveil the nexus between electricity use, environmental policies, and financial development to report novel approaches through the lens of sustainable development. The present research examines the heterogeneous impacts of climate policies and ecological taxes on financial development. In doing so, the study has considered greener energy and institutional quality variables as policy factors for financial development. The authors employ the 29 OECD economies data from 1994 to 2020. This research gathered the data from authentic sources such as the OECD, the World Bank, and ICRG. The pre-estimation diagnostic (residual cross-section dependence, unit root, and cointegration) tests asserted cross-section dependence between countries, variables’ stationarity, and cointegration between the variables. Due to the asymmetrical behaviour of data shown by the Jarque and Bera (Int Stat Rev 55:163–172, 1987) test, this study uses non-parametric panel quantile regression. It asserts environmental policies and green electricity use have a substantial yet mixed influence on financial development. In contrast, trade openness and GDP are the significant factors of economic development in the region. Overall, Environmental taxes adversely affect financial development in developed countries across quantiles. This study suggests promoting and improving green investment, trade, and efficient environmental policies to encourage financial development in developed countries without affecting ecological quality.
Keywords: Environmental policies; Environmental regulations; Environmental taxes; Financial development; Green electricity; Sustainable development